Stress and Anxiety : Applications to Schools, Well-Being, Coping, and Internet Use. - Moore, Kathleen A. (Logos Verlag Berlin, 2015)
Long description: The current volume in the Stress and Anxiety series focuses on peer-reviewed papers in four thematically different areas. The first collection of papers relates to a range of issues in schools and school children: stress and coping among preschoolers, among children aged 7-11 years and those children with at risk behaviours and those experiencing test anxiety, as well as stress and intention to quit among teachers. Next is the impact of stress on people's well-being in particular stress, and economic deprivation in particular, as predictors of depression and on cardiovascular reactivity. Coping, including resilience and adjustment, is addressed in the third section where there is an emphasis on appraisal, cognitions and comedy. The final chapters are contemporaneous as they present two opposing views on the internet and cyberspace: the internet as social support coping, alternatively as an escape or avoidant strategy.